Bioactive Components Analysis and Pharmacological Properties of Extracts and Metabolites of Lichen Umbilicaria crustulosa - Jovica Tomović; Aleksandar Kočović; Marijana Anđić; Jovana Bradić; Nevena Zubić; Vladimir Jakovljević; Miroslav Sovrlić; Perica Vasiljević; Nedeljko Manojlović (MDPI AG, 2024)
Lichens, a diverse group of organisms, have a unique structure consisting of fungal filaments and photosynthetic partner cells. This research conducted a comprehensive chemical analysis and evaluation of the anti-inflammatory and antioxidant properties of methanolic and acetone extracts from Umbilicaria crustulosa lichen, along with its isolated metabolites. The process involved separating atranorin and chloratranorin fractions, physodic acid, and gyrophoric acid. Secondary metabolites were identified using chromatographic and spectroscopic data. The total polyphenols content was determined spectrophotometrically. This study examined the antioxidant activity of extracts of the lichen U. crustulosa and the isolated fractions using three methods: DPPH scavenging activity, ABTS scavenging activity, and reducing power. This study also evaluated the acute oral toxicity and the anti-inflammatory activity of the extracts in Wistar albino rats. A higher content of the total phenolic compounds was found in the acetone extract, but antioxidant and anti-inflammatory activities were more prominent in the methanolic extract. The isolated atranorin and chloratranorin fractions and compound physodic acid showed the highest antioxidant activity. No toxic effects were noted in the acute oral toxicity study. This study highlights the potential of the investigated lichen as a valuable source of novel biological agents.